Movement Behavior Patterns in People With First-Ever Stroke. Issue 12 (December 2019) - Wondergem, Roderick; Veenhof, Cindy; Wouters, Eveline M.J.; de Bie, Rob A.; Visser-Meily, Johanna M.A.; Pisters, Martijn F.
Abstract : Background and Purpose—: Movement behaviors, that is, both physical activity and sedentary behavior, are independently associated with health risks. Although both behaviors have been investigated separately in people after stroke, little is known about the combined movement behavior patterns, differences in these patterns between individuals, or the factors associated with these patterns. Therefore, the objectives of this study are (1) to identify movement behavior patterns in people with first-ever stroke discharged to the home setting and (2) to explore factors associated with the identified patterns. Methods—: Cross-sectional design using data from 190 people with first-ever stroke discharged to the home setting. Movement, behavior was measured over 2 weeks using an accelerometer. Ten movement behavior outcomes were calculated and compressed using principal component analysis. Movement behavior patterns were identified using a k-means clustering algorithm. Demographics, stroke, care, physical functioning, and psychological, cognitive and social factors were obtained. Differences between and factors associated with the patterns were investigated. Results—: On average, the accelerometer was worn for 13.7 hours per day. The average movement behavior of the participants showed 9.3 sedentary hours, 3.8 hours of light physical activity, and 0.6 hours of moderate-vigorous physical activity. Three patterns and associated factors were identified: (1) sedentary exercisers (22.6%), with a relatively low age, few pack-years, light drinking, and high levels of physical functioning; (2) sedentary movers (45.8%), with less severe stroke symptoms, low physical functioning and high levels of self-efficacy; and (3) sedentary prolongers (31.6%), with more severe stroke symptoms, more pack-years, and low levels of self-efficacy. Conclusions—: The majority of people with stroke are inactive and sedentary. Three different movement behavior patterns were identified: sedentary exercisers, sedentary movers, and sedentary prolongers. The identified movement behavior patterns confirm the hypothesis that an individually tailored approach might be warranted with movement behavior coaching by healthcare professionals. Abstract : Supplemental Digital Content is available in the text.